Changing Epidemiology of Neonatal Septic Arthritis - SS Deshpande; N Taral; N Modi; M Singrakhia (Journal of Orthopaedic Surgery, 2004)
Purpose. To study the changing epidemiological pattern of micro-organisms as an aetiology of septic arthritis, and to correlate the pattern with the outcome of neonatal septic arthritis, in terms of joint function and morphology. Methods. 15 consecutive cases of neonatal septic arthritis of hip admitted between 1999 and 2002 were studied. Diagnosis of septic arthritis was made on the basis of Morrey's criteria. All patients were treated by arthrotomy after aspiration of purulent fluid from the joint. Patients were followed up for a mean period of 2.4 years. Clinical and radiological examinations were performed at follow-up. Results. The mean age of the 15 patients was 20.35 days. 13 (87%) patients had primary septic arthritis, while only 2 (13%) had associated osteomyelitis. Culture reports revealed that the spectrum consisted of 33% gram-negative organisms, 7% fungal, and only 20% gram-positive organisms— Staphylococcus aureus in 3 patients, Klebsiella in 2 patients, one each of Proteus, Candida, Escherichia coli , and Enterobactor. Six patients were pus-cell positive with negative culture. No organism was found in 6 (40%) cases. Investigations showed leukocytosis, raised C-reactive protein and erythrocyte sedimentation rate in all 15 patients. 12 patients had normal clinical and radiological parameters at follow-up. Three patients had delayed surgical drainage of more than 72 hours due to late presentation, and showed various radiological sequelae with terminal restriction of joint movements. Conclusion. There are more cases of primary septic arthritis than secondary septic arthritis. Clinicians should be alert of the aetiology shift to gram-negative organisms, in addition to fungal and gram-positive ones. Arthrotomy to drain pus from the joint should not be delayed. Better long-term results can be achieved by early surgical drainage and immediate antibiotic coverage.